Examining determinants of women’s labor participation rate in developing Asian countries - Febriano Aulia Nur Rahmawan; Siti Aisyah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The study aims to analyze the impact of women's involvement in parliament, women's education, fertility rates, female unemployment, and female entrepreneurship on the female labor participation rate in developing countries in Asia.Method — This research is quantitative study utilizing secondary data obtained from the World Bank Indicators. The data collection involves documentation and literature review. The methodology employed is panel data analysis with a Fixed Effects Model (FEM) for six developing countries in the Southeast Asia and East Asia region for the period of 2011 to 2021. The data are processed using the Eviews 10 application.Result — Our findings indicate that women's involvement in parliament has a positive and significant impact on the female labor participation rate. Conversely, the female unemployment rate has a negative and significant effect on the female labor participation rate. Meanwhile, women's education, fertility rate, and female entrepreneurship show no significant impact on the female labor participation rate.Novelty — While a number of studies have explored the factors influencing the female labor participation rate, research on labor force participation rates in Southeast and East Asia has yielded inconsistent results. Hence, there is a need for further investigation to fill this knowledge gap, providing a deeper understanding of the factors influencing the female labor participation rate in the context of developing nations.